Refleksi Memorandum of Understanding (MoU) Helsinki Dalam Kaitan Makna Otonomi Khusus Di Aceh - Zaki 'Ulya (The Constitutional Court of the Republic of Indonesia, 2014)
After the implementation of regional autonomy reforms focused on provincial autonomy in establishing their own households. According to the concept of autonomy is divided into three autonomous ordinary, special autonomy and autonomy, which is emphasized in Article 18, 18A and 18B of the 1945 Constitution. Reasons for granting the status of special autonomy in Aceh, one of which was to eliminate the GAM movement which aims to separate itself from the Homeland. Granting autonomy status is determined through of the Helsinki MoU is transformed in Law No. 11 of 2006. The method used is the juridical normative. This research approach statutory (statute approach), approach the case (case approach). Based on the analysis conducted found that the existence of the MoU are set forth in the Law. 11 The year 2006 is a manifestation lifting values into privilege in Aceh, as well as adding some other peculiarities such as local politics. Aceh has a specificity and privileges in Law No. 11 In 2006, the emblem and flag of determining the area.